The effect of alternate nostril breathing exercise in vital signs of congestive heart failure patients - Simandalahi, Tiurmaida; Morika, Honesty Diana; Fannya, Puteri (International Journal Of Community Medicine And Public Health, 2019)
Background: Changes in vital signs such as tachycardia, dyspnea, tachipnea, decreased oxygenation, caused by the inability of the heart to pump enough blood to meet the needs of oxygen and nutrients needed by the tissue, so that alternative therapies are needed: alternate nostril breathing exercise (ANBE) as a companion to pharmacological therapy for congestive heart failure (CHF) patients. The purpose of this study was to see the effect of ANBE on the vital sign of CHF patients. Methods: This Quasy experimental study was used one group pretest and Posttes design, conducted at one of the Padang City Hospitals from March to August 2019. Study population includes CHF sufferers, with a sample of 16 people, using accidental sampling technique. Univariate data analysis to get the mean of vital sign and bivariate measurements using parametric test i.e. Paired t-test to see the effect of this therapy. Results: Mean vital signs pretest and posttest was given in a row The observations are: respiratory rate (RR): 5.4978; 4.6078, pulse: 10.1804; 8,7770, systolic blood pressure (SBP): 12,5963; 11,1481, and diastolic blood pressure (DBP): 10,3009; 8.8606. Paired t-test obtained p-value of RR, pulse, SBP and DBP: 0.000, and existing t count> from t table (t count> 2.13145), so that there is an effect of ANBE on vital signs. Conclusions: ANBE affects the vital sign of CHF patients and can be continued as an intervention that can be carried out independently by CHF sufferers.